A new qualitative acoustic emission parameter based on Shannon's entropy for damage monitoring. (1st February 2018) - Chai, Mengyu; Zhang, Zaoxiao; Duan, Quan
Highlights: A new AE parameter based on Shannon's entropy is proposed for damage monitoring. The parameter, i.e. AE entropy, is independent of threshold and time-driven parameters. The feasibility of AE entropy is successfully validated by fatigue and bending tests. AE entropy is more effective to discriminate different damage stages than AE amplitude. Critical damages are identified by the occurrence of a sudden increase of AE entropy. Abstract: An important objective of acoustic emission (AE) non-destructive monitoring is to accurately identify approaching critical damage and to avoid premature failure by means of the evolutions of AE parameters. One major drawback of most parameters such as count and rise time is that they are strongly dependent on the threshold and other settings employed in AE data acquisition system. This may hinder the correct reflection of original waveform generated from AE sources and consequently bring difficulty for the accurate identification of the critical damage and early failure. In this investigation, a new qualitative AE parameter based on Shannon's entropy, i.e. AE entropy is proposed for damage monitoring. Since it derives from the uncertainty of amplitude distribution of each AE waveform, it is independent of the threshold and other time-driven parameters and can characterize the original micro-structural deformations. Fatigue crack growth test on CrMoV steel and three point bending test on a ductile material are conducted to validate the feasibility and effectiveness of the proposed parameter. The results show that the new parameter, compared to AE amplitude, is more effective in discriminating the different damage stages and identifying the critical damage.